2022
DOI: 10.1017/s1049023x22000140
|View full text |Cite
|
Sign up to set email alerts
|

Terrorist Attacks Against Emergency Medical Services: Secondary Attacks are an Emerging Risk

Abstract: Introduction: Terrorists increasingly aim at so-called soft targets, such as hospitals. However, little is known about terrorist attacks against Emergency Medical Services (EMS). Objective: This study aims to review all documented terrorist attacks against EMS that occurred world-wide from 1970-2019 using the Global Terrorism Database (GTD). Methods: Reports of terrorist attacks against EMS were extracted from the GTD from 1970-2019. Data collection included temporal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Since the start of the Ukrainian war, multiple attacks against healthcare workers and facilities have been reported [ 3 ]. Ambulances have been shot at, hindered, used as Trojan horses and targeted in secondary attacks, something witnessed in other acts of terrorism [ 9 , 10 ], and multiple hospitals have sustained indiscriminate or deliberate attacks, all certifying that this invasion constitutes hybrid warfare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the start of the Ukrainian war, multiple attacks against healthcare workers and facilities have been reported [ 3 ]. Ambulances have been shot at, hindered, used as Trojan horses and targeted in secondary attacks, something witnessed in other acts of terrorism [ 9 , 10 ], and multiple hospitals have sustained indiscriminate or deliberate attacks, all certifying that this invasion constitutes hybrid warfare.…”
Section: Discussionmentioning
confidence: 99%
“…After the 2022 Russian invasion of Ukraine, the UHC team concentrated on war-related initiatives, collecting, verifying and documenting data points similar to those published in many recent CTM research articles: attack modalities and weapons used, death and injury tolls, and damage sustained to critical health infrastructure [ 9 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies found four terrorist attacks against Emergency Medical Services (EMS) in Eastern Europe from 1970 through 2019 (two percent of 184 world-wide attacks) and 13 terrorist attacks against hospitals in the region (three percent of 454 world-wide attacks). 19,20 During the Russo-Ukrainian war, over one-third of the hospitals and clinics in the Donbas region of Ukraine had been damaged or destroyed from early 2014 through 2017. 21 Chechen separatists' suicide bombing attacks in 2010 on Moscow's transport system, a combination that is particularly lethal, ISIL's 2017 St Petersburg Metro bombing, and the escalation of the Russo-Ukrainian conflict in early 2022 are all causes for concern for modern-day Russia and the surrounding region's health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…From 1970 through 2019, there were 454 terrorist attacks against hospitals and 148 terrorist attacks against Emergency Medical Services causing 2,381 fatalities and 4,016 injured. 1,2 In the same period, vaccinators have been targeted 133 times, most of which have occurred since 2010. 3 Despite their pivotal role in health care, little is known about the risk for primary care providers (PCPs) and their offices as targets of terrorism.…”
Section: Introductionmentioning
confidence: 99%